Pendidikan Pembebasan menurut Paulo Freire dan Penerapannya dalam Pendidikan Agama Kristen: Sebuah Kolaborasi Pendidikan Guru-Murid - Frets Keriapy; Talizaro Tafonao (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
Education is an important thing in a society, even a country. Without education, the future of a country will be destroyed (collapsed). Therefore, education must be a serious concern to educate the nation. By using a literature-based qualitative research method, the author examines the pedagogy of liberation promoted by Paulo Freire. Pedagogy of liberation is then applied in Christian Education. From the resulting study, the author found that the pedagogy of liberation can be applied in Christian education to avoid an education system that makes the teacher the center of learning (bank-style education system) so that it can be avoided of oppression action.